The Spanish coast: more than a quarter of a century adrift - García García, Miriam (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
Still under the effects of the hangover of the most intense financial and real estate crisis suffered in Spain, which has left on the Spanish coast a badly damaged landscape, its roots are investigated. For this, it is necessary to go back to the origins and the subsequent evolution of the legal framework that regulates in the country the protection of the coast and urban planning. All this in a political and socio-economic context that, as will be seen, has found in urban planning legislation and in the skeletal territorial planning of the coast the necessary complicity for the devastation of a large part of the coastal system. Despite the fact that, in our time, practically all the coastal regions of Spain have some instrument of protection and management of their coasts, their scope is insufficient and inconsistent with the global context of climate change and the growing social demand for a landscape that makes sense from the point of view of its ecological functionality and capacity for social use.
Keywords: Coastline; Coast; Territorial planning; Climate change; Landscape